Gender perspective of HIV/AIDS Knowledge and sexual behaviour of adolescents with hearing impairment in selected special schools in Ghana - Issaka, Alimatu Cecilia (Advances in Social Sciences Research Journal, 2018)
Hearing impaired youth are equally susceptible to the dangers posed by the Human Immunodeficiency Virus (HIV) and Acquired Immunodeficiency Syndrome (AIDS). The rate of contraction of the disease among adolescents with hearing impairment rests on the knowledge and sexual behaviours of the individuals. Gender and sociocultural issues are critical in facilitating adolescents’ access to reproductive information and education. This study examined knowledge of HIV/AIDS and sexual behaviour of adolescents among the hearing impaired in selected special schools in Ghana. Mixed methodological design was employed in gathering both qualitative and quantitative data from 310 respondents. Findings of the study revealed that females with hearing impairment have better HIV/AIDs knowledge than their male colleagues. Female students considered more vulnerable frequently receive sex education from their parents, school authorities and from their peers.